2018
DOI: 10.2478/raon-2018-0037
|View full text |Cite
|
Sign up to set email alerts
|

Immune RECIST criteria and symptomatic pseudoprogression in non-small cell lung cancer patients treated with immunotherapy

Abstract: BackgroundUncommon response during immunotherapy is a new challenging issue in oncology practice. Recently, new criteria for evaluation of response to immunotherapy immune response evaluation criteria in solid tumors (iRECIST) were accepted. According to iRECIST, worsening of performance status (PS) accompanied to pseudoprogression reflects most probably the true progression of the malignant disease.MethodsA systematic review of the literature was made by using several electronic database with the following se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 37 publications
0
29
0
Order By: Relevance
“…One of them is pseudoprogression, which is described as a radiological progression that is followed by stabilization or response on the next imaging. 18 In Keynote-001 trial, the incidence of tumour pseudoprogression was 7.3%. 19 In our analysis, we did not collect data on this atypical response, therefore its influence on the response rate cannot be established.…”
Section: Discussionmentioning
confidence: 99%
“…One of them is pseudoprogression, which is described as a radiological progression that is followed by stabilization or response on the next imaging. 18 In Keynote-001 trial, the incidence of tumour pseudoprogression was 7.3%. 19 In our analysis, we did not collect data on this atypical response, therefore its influence on the response rate cannot be established.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, responding patients with PD-L1 negative tumours as well as non-responding patients with PD-L1 positive tumours have been reported during the course of anti-PD-L1 therapy [5,6]. Adding to this, assessing responses to immunotherapy by standard RECIST criteria may be challenging compared with conventional chemotherapy as tumour cells are not killed directly and the fact that pseudo progression often is observed in patients receiving immune checkpoint inhibitors [7][8][9].…”
Section: This Article Is Part Of the Topical Collection On Preclinicamentioning
confidence: 99%
“…However, a recent review by Vrankar et al reported the "symptomatic pseudoprogression" in eight NSCLC patients treated with anti-PD-1/PD-L1 therapy. 42 These eight patients experienced psuedoprogression accompanied with clinical deterioration, followed by clinical benefit after 4-20 weeks after treatment onset. According to iRECIST, treatment beyond progression per RECIST 1.1 should only be allowed in patients with a stable clinical status.…”
Section: Symptomatic Pseudoprogressionmentioning
confidence: 95%
“…Immune RECIST might fail to capture pseudoprogression, particularly in patients with “symptomatic pseudoprogression.” In general, pseudoprogression should not be accompanied with the deterioration of clinical status, which usually indicates the true progression. However, a recent review by Vrankar et al reported the “symptomatic pseudoprogression” in eight NSCLC patients treated with anti‐PD‐1/PD‐L1 therapy . These eight patients experienced psuedoprogression accompanied with clinical deterioration, followed by clinical benefit after 4‐20 weeks after treatment onset.…”
Section: The Role Of Medical Imaging In Immunotherapy: Response Assesmentioning
confidence: 99%